2007
DOI: 10.1111/j.1365-2133.2007.08356.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal involvement in pemphigus vulgaris: a clinical study of 77 cases

Abstract: Involvement of the female genital tract with PV might not be as infrequent as was previously thought; it is probably the second most common mucosal site of PV after the oral mucosa. Genital lesions may be missed and the need for thorough pelvic examination should not be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
3
33
4
2
Order By: Relevance
“…7,9,10 Yapı-lan az sayıdaki çalışmada farklı tutulum oranları bildirilmiş-tir. 3,11,12 Marren ve arkadaşları dokuz pemfigus vulgarisli hastanın dördünde vulva tutulumu olduğunu belirtirken 11 Malik ve Ahmed sadece genital bölge tutulumlu pemfiguslu hastalarla yaptıkları çalışmada pemfigusta genital tutulumun nadir olduğunu ve vajinal lezyonlardan ziyade vulva tutulumunun daha fazla olduğunu bildirmişlerdir. Hastaların %61'inde labial tutulum, %30'unda vajinal tutulum, %3'ünde ise sadece vajinal tutulum saptanmış-tır.3 Genital bölge tutulumu nadir olmakla birlikte yapı-lan bir diğer çalışmada 77 pemfigus vulgarisli hastanın 39'unda (%51) genital bölge tutulumu tespit edilerek oral mukozadan sonra ikinci en sık tutulan mukozal bölge olduğu öne sürülmüştür.…”
Section: Discussionunclassified
“…7,9,10 Yapı-lan az sayıdaki çalışmada farklı tutulum oranları bildirilmiş-tir. 3,11,12 Marren ve arkadaşları dokuz pemfigus vulgarisli hastanın dördünde vulva tutulumu olduğunu belirtirken 11 Malik ve Ahmed sadece genital bölge tutulumlu pemfiguslu hastalarla yaptıkları çalışmada pemfigusta genital tutulumun nadir olduğunu ve vajinal lezyonlardan ziyade vulva tutulumunun daha fazla olduğunu bildirmişlerdir. Hastaların %61'inde labial tutulum, %30'unda vajinal tutulum, %3'ünde ise sadece vajinal tutulum saptanmış-tır.3 Genital bölge tutulumu nadir olmakla birlikte yapı-lan bir diğer çalışmada 77 pemfigus vulgarisli hastanın 39'unda (%51) genital bölge tutulumu tespit edilerek oral mukozadan sonra ikinci en sık tutulan mukozal bölge olduğu öne sürülmüştür.…”
Section: Discussionunclassified
“…Genital tract lesions have also been described in PV, but almost invariably in women. Akhyani et al (12) observed genital involvement in 51%, almost invariably showing extensive mucocutaneous involvement. After the oral mucosa, genital mucosa might thus represent the second most commonly affected mucosal site in PV, and its involvement is surely under-diagnosed (12).…”
Section: Included In the Theme Issue: Venereology -Not To Be Forgottenmentioning
confidence: 99%
“…Akhyani et al (12) observed genital involvement in 51%, almost invariably showing extensive mucocutaneous involvement. After the oral mucosa, genital mucosa might thus represent the second most commonly affected mucosal site in PV, and its involvement is surely under-diagnosed (12). Finally, the presence of genital lesions was associated with treatment-resistance and regarded as a poor prognostic factor and marker of disease severity (9).…”
Section: Included In the Theme Issue: Venereology -Not To Be Forgottenmentioning
confidence: 99%
“…The other mucosal areas, nasal cavity, larynx (epiglottis, vocal cords), oropharynx, esophagus, vagina, vulva, penis, and anus may also be affected [1,13]. Epistaxis and hoarseness are present owing to the involvement of the nose, pharynx, and larynx [1,13,[35][36][37]. Genital mucosa is one of the frequent sites involved in PV after the oral mucosa [37].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Epistaxis and hoarseness are present owing to the involvement of the nose, pharynx, and larynx [1,13,[35][36][37]. Genital mucosa is one of the frequent sites involved in PV after the oral mucosa [37].…”
Section: Clinical Featuresmentioning
confidence: 99%